Atributos da solução e do solo de cerrado após aplicação de resíduo da extração de celulose - Maciel, Thais Monique de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The great expansion of industry and the consumer market has led, in recent decades, the generation of large amounts of waste. With the production of cellulose and paper the industries in the sector have generated daily large amounts of solid waste and effluents, thus becoming a major environmental and economic concern. In order to return with these by-products in a sustainable manner to nature, the purpose of the study was to evaluate, under greenhouse conditions, using soil columns and cycles of wetting, the effect of residues from the cellulose extraction in the soil physical and chemical attributes and chemical soil solution, especially those related to the scattering of two Oxisols different texture. The experiment was established at the Faculty of Engineering, Campus Ilha Solteira, University of Sao Paulo State (UNESP), located in the municipality of Ilha Solteira, Sao Paulo State, Brazil. The experimental design was completely randomized, with 7 treatments and 4 replicates for each soil. The treatments were: T1 - without the addition of lime and residue (control), T2 - 1.0 t ha-1 of limestone, T3 - 1.2 t ha-1 dregs/grits, T4 - 0.8 t ha-1 of lime mud; T5 - 2.4 t ha-1 ash, T6 - 1.8 t ha-1 dregs/grits + lime mud + ash in the ratio 1:3: 6, T7 – 1.0 t ha-1 dregs/grits + lime mud in the ratio 1:3. The soil was collected and characterized chemically and physically before the period of the experiment. During the incubation period was assessed soil matric potential by tensiometers and chemical composition of the extracted soil solution. After this period, dismounted the soil columns and the physical attributes were evaluated: distribution and aggregate stability, soil porosity, soil bulk density, particle size and also the soil chemical attributes: OM, pH, K, Ca, Mg, Na, H + Al, Al . The BS, CEC and Base saturation % were calculated. The results were analyzed by performing analysis of variance and ...

A grande expansão das indústrias e do mercado consumidor tem provocado, nas últimas décadas, a geração de elevadas quantidades de resíduos. Com a produção de papel e celulose, as indústrias do setor têm gerado diariamente grandes quantidades de resíduos sólidos e efluentes, constituindo-se em uma grande preocupação ambiental e econômica. No intuito de retornar com estes subprodutos de forma sustentável à natureza, o objetivo do estudo foi avaliar, em casa de vegetação usando colunas de solo e ciclos de umedecimento, o efeito da aplicação de resíduos da extração de celulose nos atributos físicos do solo e químicos da solução e do solo, especialmente aqueles relacionados à dispersão de argila de dois Latossolos Vermelhos. O experimento foi implantado na Faculdade de Engenharia, Campus de Ilha Solteira (UNESP), localizada no município de Ilha Solteira, SP. O delineamento experimental utilizado foi inteiramente casualizado, com 7 tratamentos e 4 repetições, para cada solo. Os tratamentos utilizados foram: T1 – sem adição de calcário e resíduo (controle); T2 – 1,0 t ha-1 de calcário calcítico; T3 – 1,2 t ha-1 de dregs/grits; T4 – 0,8 t ha-1 de lama cal; T5 – 2,4 t ha-1 de cinza; T6 – 1,8 t ha-1 de dregs/grits + lama cal + cinza na proporção 1:3:6; T7 – 1,0 t ha-1 de dregs/grits + lama cal na proporção 1:3. O solo foi coletado e caracterizado química e físicamente antes do período do experimento. Durante o período de incubação foi avaliado o potencial matricial do solo por meio de tensiômetros e a composição química da solução extraída de cada solo estudado por extratores de solução. Após esse período, desmontando as colunas de solo, foram avaliados os atributos físicos: distribuição e estabilidade de agregados, porosidade do solo, densidade do solo, granulometria e também os atributos químicos solo: MO, pH, K, Ca, Mg, Na, H + Al, Al. A ...
Keywords: Solos - Manejo; Residuos organicos - Reaproveitamento; Fisica do solo; Quimica do solo; Organic wastes Recycling